2019
DOI: 10.1186/s12913-019-4423-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobile sexual health services for adolescents: investigating the acceptability of youth-directed mobile clinic services in Cape Town, South Africa

Abstract: Background The Human Immunodeficiency Virus (HIV) epidemic is growing rapidly among South African adolescents and young adults (AYA). Although HIV counselling and testing, HIV prevention and treatment options are widely available, many AYA delay health-seeking until illness occurs, demonstrating a need for youth responsive, integrated sexual and reproductive health services (SRHS). While feasibility and cost-effectiveness have been evaluated, acceptability of mobile clinics among AYA has yet to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
3
24
1
Order By: Relevance
“…There is potential public health benefit in providing routine screening for these chronic diseases which are associated with disability and mortality. Since mobile clinics are cost-effective [ 39 ], have high levels of acceptability [ 41 ], and units can be directed to high disease burden areas, these may serve as effective diagnostic units that can offer earlier disease detection, associated with earlier treatment and care [ 12 , 19 ]. Subsequent disease management requires meticulous planning to ensure logistical support and follow-up for patients who require community-based care, and referral for those who may prefer more conventional care settings [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is potential public health benefit in providing routine screening for these chronic diseases which are associated with disability and mortality. Since mobile clinics are cost-effective [ 39 ], have high levels of acceptability [ 41 ], and units can be directed to high disease burden areas, these may serve as effective diagnostic units that can offer earlier disease detection, associated with earlier treatment and care [ 12 , 19 ]. Subsequent disease management requires meticulous planning to ensure logistical support and follow-up for patients who require community-based care, and referral for those who may prefer more conventional care settings [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the clinic could ensure confidentiality of patient medical records and privacy in the consultation room, the public nature of the clinic meant that patients’ attendance was visible. However, a recent study conducted with adolescents and young adults attending a mobile service showed that most (96%) rated the service as confidential [ 41 ]. Future research could investigate methods of providing HIV services that would increase uptake for those who are even harder to reach and for those who have reasons to avoid knowing their status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based mobile health clinics (CMHC) are an important model for delivering health services to vulnerable populations and impactful when providing differentiated, tailored and client-centered preventative health services [ 19 21 ]. In low- and middle-income countries, mobile health clinics have been deployed to provide a wide range of public health services; including cervical cancer screening in Thailand [ 22 ] and Brazil [ 23 ], maternal and child health care in Tanzania [ 24 ], primary health care in Namibia [ 25 ] and Malawi [ 26 ], mental health and diabetes screening and services in India [ 27 , 28 ], and HIV screening and sexual and reproductive health services in South Africa [ 29 , 30 ]. CMHC that provide comprehensive integrated SRHS may be especially attractive to AGYW, providing flexibility in location to increase accessibility for these populations in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our familiarity with HIV acts to bring it in line with a number of other youth-associated health concerns, such as diabetes and becoming pregnant, that may feel as, or sometimes more, concerning [12,15]. As a generation that is used to owning one mobile device that caters to a full spectrum of needs and an online portal that is simultaneously our library, shopping mall and social club, having our health needs separated into different visits, clinics and professionals seems odd and difficult to manage.…”
mentioning
confidence: 99%